2018
DOI: 10.21608/jfds.2018.77776
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Borago Extracts against Indomethacin-Induced Gastric Ulcer in Rats

Abstract: Gastric ulcer stays one of the perilous sicknesses in the world. In spite of the fact that there are numerous medications utilized for the treatment of gastric ulcer, the vast majority of these deliver a few adverse impacts. The aim of this investigation was to assess the antiulcer effects of Borago (Borago officinalis L) leaves extract (BL), flowers extract (BF) and the mixture of leaves and flowers extracts (Mix) against gastric ulcer induced by indomethacin in rats and compared with ranitidine as a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These effects seem to be due to the antioxidant properties of phenolic glycosides, flavonoids, and tannins present in the extracts. In our experimental stress-induced gastric ulcer model, the Borago extracts were able to significantly protect the gastric mucosa from the stress damage, confirming the finding of Gazwi and Mahmoud ( 17 ). In particular, we showed that all the extracts were able to decrease the severity and the number of stress ulcers.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These effects seem to be due to the antioxidant properties of phenolic glycosides, flavonoids, and tannins present in the extracts. In our experimental stress-induced gastric ulcer model, the Borago extracts were able to significantly protect the gastric mucosa from the stress damage, confirming the finding of Gazwi and Mahmoud ( 17 ). In particular, we showed that all the extracts were able to decrease the severity and the number of stress ulcers.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, it has been reported that Borago officinalis extracts may have a gastroprotective effect against indomethacin-induced gastric ulcers ( 17 ). These effects seem to be due to the antioxidant properties of phenolic glycosides, flavonoids, and tannins present in the extracts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations